EXTH-46. ARTIFICIAL INTELLIGENCE-BASED IDENTIFICATION OF COMBINED VANDETANIB AND EVEROLIMUS IN THE TREATMENT OF ACVR1-MUTANT DIFFUSE INTRINSIC PONTINE GLIOMA. (9th November 2020) - Carvalho, Diana; Richardson, Peter; Olaciregui, Nagore Gene; Stankunaite, Reda; Lavarino, Cinzia Emilia; Molinari, Valeria; Corley, Elizabeth; Ruddle, Ruth; Donovan, Adam; Pal, Akos; Raynaud, Florence I; Overington, John P; et al.
Abstract: Somatic mutations in ACVR1, encoding the serine/threonine kinase ALK2 receptor, are found in a quarter of children with the currently incurable brain tumour diffuse intrinsic pontine glioma (DIPG). Treatment of ACVR1 -mutant DIPG patient-derived models with multiple inhibitor chemotypes leads to a reduction in cell viability in vitro and extended survival in orthotopic xenografts in vivo, though there are currently no specific ACVR1 inhibitors licensed for DIPG. Using an Artificial Intelligence-based platform to search for approved compounds which could be used to treat ACVR1-mutant DIPG, the combination of vandetanib and everolimus was identified as a possible therapeutic approach. Vandetanib, an approved inhibitor of VEGFR/RET/EGFR, was found to target ACVR1 (Kd=150nM) and reduce DIPG cell viability in vitro, but has been trialed in DIPG patients with limited success, in part due to an inability to cross the blood-brain-barrier. In addition to mTOR, everolimus inhibits both ABCG2 (BCRP) and ABCB1 (P-gp) transporter, and was synergistic in DIPG cells when combined with vandetanib in vitro . This combination is well-tolerated in vivo, and significantly extended survival and reduced tumour burden in an orthotopic ACVR1 -mutant patient-derived DIPG xenograft model. Based on these preclinical data, three patients with ACVR1 -mutant DIPG were treated with vandetanib and everolimus. These cases may inform on the dosing and the toxicity profile of this combination for future clinical studies. This bench-to-bedside approach represents a rapidly translatable therapeutic strategy in children with ACVR1 mutant DIPG.